2016
DOI: 10.1016/j.jaci.2015.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Calcium spirulan derived from Spirulina platensis inhibits herpes simplex virus 1 attachment to human keratinocytes and protects against herpes labialis

Abstract: These data indicate a potential clinical use of Ca-SP containing Spirulina species extract for the prophylactic treatment of herpes labialis and suggest possible activity of Ca-SP against infections caused by other herpesviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 35 publications
3
57
0
Order By: Relevance
“…SCEM exhibited antiviral activity against HCV and this was in agreement with other study which showed the antiviral activities of water extract of S. platensis against hepatitis A and herpes simplex viruses [8] as well as the antiviral activity of calcium spirulan (Ca-SP) which exhibited a strong inhibitory against several enveloped viruses, by targeting the viral absorption/penetration and some replication stages after penetration into cells [12,32]. Moreover, a comparative clinically trial of S. platensis revealed that Spirulina decrease more significantly the HCV virus load at least 2-log 10 and also significantly improved alanine aminotransferase [9].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…SCEM exhibited antiviral activity against HCV and this was in agreement with other study which showed the antiviral activities of water extract of S. platensis against hepatitis A and herpes simplex viruses [8] as well as the antiviral activity of calcium spirulan (Ca-SP) which exhibited a strong inhibitory against several enveloped viruses, by targeting the viral absorption/penetration and some replication stages after penetration into cells [12,32]. Moreover, a comparative clinically trial of S. platensis revealed that Spirulina decrease more significantly the HCV virus load at least 2-log 10 and also significantly improved alanine aminotransferase [9].…”
Section: Discussionsupporting
confidence: 90%
“…Among these polysaccharides, calcium spirulan (Ca-SP) exhibited strong inhibitory effect against some enveloped viruses [12], beside it could suppress the replication of herpes simplex, mumps, measles, influenza A viruses and cytomegalovirus [13]. In addition to inhibit metastasis of mouse B16 melanoma cells [14], the polysaccharide from Spirulina species acts as hepatoprotectant against malignant cell [15].…”
mentioning
confidence: 99%
“…; König ; Mader et al . ). Ganc was found to inhibit mammalian cell proliferation in vitro at IC 50 concentrations ranging from 10.21 to >250 μg mL −1 (FDA ).…”
Section: Discussionmentioning
confidence: 97%
“…; König ; Mader et al . ). However, the IC 50 was approximately 4 to 10‐times higher than determined for the extracellular fractions.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Spirulina has well-known culture conditions and has been used in food formulations or extraction of biocomposites. Studies have shown different biological actions can be identified on components of this microalga and its antifungal and antibacterial properties have being exploited [5,34,97,98].…”
Section: Microalgae As Potential Source Of Preservativesmentioning
confidence: 99%